2007
DOI: 10.1088/0031-9155/52/11/001
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulations of the dosimetric impact of radiopaque fiducial markers for proton radiotherapy of the prostate

Abstract: Many clinical studies have demonstrated that implanted radiopaque fiducial markers improve targeting accuracy in external-beam radiotherapy, but little is known about the dose perturbations these markers may cause in patients receiving proton radiotherapy. The objective of this study was to determine what types of implantable markers are visible in setup radiographs and, at the same time, perturb the therapeutic proton dose to the prostate by less than 10%. The radiographic visibility of the markers was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
95
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(107 citation statements)
references
References 24 publications
(28 reference statements)
9
95
2
Order By: Relevance
“…The effect may be minimal, but some reports suggest that using gold FM dose may be reduced by as much as 20% using photons 39 and reduced by up to 85% in proton therapy in the area immediately around the FM. 40 Many authors have reported studies based on the use of three or four implanted gold markers. 6,7,9,12,14,41 Most studies employ three FMs placed in a 3D triangular arrangement to facilitate assessment in the three cardinal directions (Figure 2).…”
Section: Number and Types Of Fiducial Markersmentioning
confidence: 99%
“…The effect may be minimal, but some reports suggest that using gold FM dose may be reduced by as much as 20% using photons 39 and reduced by up to 85% in proton therapy in the area immediately around the FM. 40 Many authors have reported studies based on the use of three or four implanted gold markers. 6,7,9,12,14,41 Most studies employ three FMs placed in a 3D triangular arrangement to facilitate assessment in the three cardinal directions (Figure 2).…”
Section: Number and Types Of Fiducial Markersmentioning
confidence: 99%
“…The decision on which type of fiducial marker to use for the purpose of treatment positioning verification should be made based on the marker's visibility in both simulation CT and verification images, as well as the potential for dose perturbation during proton treatments 9 , 20 . To avoid these negative impacts of gold markers during treatment delivery, fiducial markers made of other materials such as carbon, polymer, and stainless steel have been introduced (CIVCO Medical Solutions, Kalona, IA).…”
Section: Discussionmentioning
confidence: 99%
“…A high‐Z marker could be even more of a problem with proton treatments, where a fiducial marker in the path of the beam could cause a shift in the Bragg peak. Several studies have calculated the magnitude of dose perturbation for proton treatments as a function of marker material, implantation depth, and orientation with respect to the beam axis for various marker materials, including gold, carbon‐coated ceramic, stainless steel, and tantalum 9 , 13 , 15 , 20 . One Monte Carlo‐based study found a 5% dose increase upstream and a 2% decrease downstream for gold markers and 250 MeV protons (15) .…”
Section: Discussionmentioning
confidence: 99%
“…The rectal balloon is used because conventional gold fiducial markers used for prostate localization in photon therapy have been shown to cause radiation dose distortion [60]. The degree of radiation distortion is greater in proton therapy, with recent studies showing that conventional gold fiducials can cause an 85% dose reduction in proton therapy [61]. Conventional gold fiducial markers also create artifacts in CT images resulting in inaccurate treatment planning.…”
Section: Proton Therapymentioning
confidence: 99%